Study of Controlled Aluminum-Vanadium Alloy Prepared by Vacuum Resistance Furnace. (9th July 2021) - Li, Lanjie; Li, Bingjun; Wan, Heli; Chen, Mao; Yee, Sze Long
Abstract : In this paper, V2 O3 is used as the raw material, and an Al-V alloy is synthesized by vacuum resistance furnace heating. The results show that with the extension of the heating time, the separation effect of the alloy and the slag and the uniformity of the alloy are significantly improved. The slag is fully separated from the alloy, and the composition of the alloy is more uniformly distributed when the heating time is controlled at 1 hour. In addition, the composition of the alloy is affected by increasing content of Al. In particular, the obtained alloy composition meets commercial standards when the mass ratio of Al is 31-36 wt%. The effect of different mass ratios of CaO on the quality of slag series and alloys was also investigated. The results show that the composition distribution of the slag system can be effectively changed with increasing the mass ratio of CaO, and the uniformity of the alloy composition is also optimized. When the mass ratio of CaO is 27 wt%, the alloy and slag are well separated, and the composition distribution in the obtained alloy is more uniform. In addition, the content of impurities in the alloy can be effectively improved under vacuum. Therefore, it is suggested that a vacuum resistance furnace should be applied in the industrial production of high-quality Al-V alloy.